Video Anomaly Detection in Crime Analysis using Deep learning Architecture- A survey - Sivakumar, G.; Mogesh, G.; Pragatheeswaran, N.; Sambathkumar, T. (Journal of Trends in Computer Science and Smart Technology, 2024)
The importance of developing automated video surveillance systems for public safety and security, particularly in crime analysis, has witnessed significant growth in recent years. This survey delves into the current landscape of automated video surveillance systems, emphasizing advancements in crime analysis and exploring existing methodologies and technologies. The study underscores the significance of employing deep learning models in video analysis. Furthermore, the study suggests a deep learning architecture to address the challenges of the existing methods. The goal of the suggested approach is to help security and law enforcement organizations quickly react to any dangers by precisely identifying unusual occurrences or actions in video sequences. The DenseNet-121 architecture is used for efficient spatial and temporal data acquisition from the video frames. This architecture is characterized by a dense connection structure in which all levels get feature mappings from all layers before them. The characteristics of DenseNet-121 can help in the accurate identification of anomalies in video streams and differentiate between normal and abnormal actions. In addition, the study also delves into the topic of using a cell structure with varied sizes to effectively split video sequences. This allows for flexible analysis and can accommodate different sorts of abnormalities. Anomaly detection accuracy can be further improved by adding size, motion, and location information to prediction and measurement models. This study serves as a foundation for the future research that aims to develop a more robust and efficient automated video surveillance solutions.
Keywords: Video Anomaly Detection; Public Safety; Security; Crime Analysis; Densenet-121